Influence of Conscientiousness Personality Trait on Mathematics Achievement among Senior Secondary School Students in North-West, Nigeria - GBENGA, Oteniya Mojeed; DANYARO, Sadiya Lawal; ALFA, Amira Ibrahim (Ilorin Journal of Education, 2024)
This study investigated influence of conscientiousness personality trait on achievement in mathematics among senior secondary school students in North-West, Nigeria. Two hypotheses were formulated and tested. Research design used was Ex post-facto. The population of the study was 487,769 senior secondary school students. A sample size of 384 was selected based on the Research Advisor Table of Population and Sample Size. Researchers administered Conscientiousness Personality Trait Scale to the students and it was found that only 77out of 384 students were found to display conscientiousness personality trait. The Conscientiousness Personality Trait Scale was used as data collection instrument. Face and convergent validity were used by the lecturers in Bayero University, Kano to validate the instrument. The convergent validity of the conscientiousness personality trait was 0.721. Students’ 1st and 2nd terms examination scores which were standardized using T-score were used as students’ achievement in mathematics. Cronbach alpha reliability index of conscientiousness personality trait was 0.726. Pearson Product Moment Correlation and t-test unrelated sample were used to analyse the data. The result of the analyses showed that there was positive significant relationship between conscientiousness personality trait (r=0.631) and mathematics achievement among senior secondary school students in North-West, Nigeria. Based on the findings of the study, it was recommended that counsellors should help guide parents and teachers on how to train children so that they can grow up with conscientiousness personality trait because it is responsible for good mathematics achievement.